1996
DOI: 10.1267/ahc.29.51
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Expression in Normal Cervical Epithelium, Cervical Intraepithelial Neoplasia and Cervical Cancer.

Abstract: With respect to the keratin expression of endocervical adenocarcinoma, keratins 8 and 19 were found in all the cases, although keratins 5, 10, 13 and 14 were not found.This result indicated that the endocervical adenocarcinoma develops from the columnar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown that each region of human cervix has a characteristic pattern of keratin gene expression in vivo (Ikegami & Kato, ; Karantza, ; Senzaki et al, ). Therefore, we examined the keratin expression of cells cultured from each cervical region to confirm their origin (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that each region of human cervix has a characteristic pattern of keratin gene expression in vivo (Ikegami & Kato, ; Karantza, ; Senzaki et al, ). Therefore, we examined the keratin expression of cells cultured from each cervical region to confirm their origin (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that each region of human cervix has a characteristic pattern of keratin gene expression in vivo (Ikegami & Kato, 1996;Karantza, 2011;Senzaki et al, 1997).…”
Section: Characterization Of Cells From Human Ectocervix Tz and Endoc...mentioning
confidence: 99%